A intersetorialidade na gestão das políticas sociais : o contexto da produção científica brasileira - Amaral, Liliane Morais (Universidade Federal de São Carlos, 2015)
Intersectoriality can be defined as an implementation strategy management actions in public, private or public / private services. In conceptual aspect, it can be understood as a political immaterial strategy for dealing with social inequalities and poverty, complex and multifactorial phenomenon, requiring therefore a complex approach. The configuration of social protection services in Brazil, built after the 1988 Constitution, sought to institutionalize social policies as universal, equitable, decentralized and democratized by means of social control, responding to the need to repay the resulting social debt policies pursued by governments authoritarian, with models of centralizing welfare and social protection. This study of exploratory and descriptive, conducted a review of published and indexed scientific literature databases in the humanities and social sciences of nature and life and related fields, in order to discuss the implementation of public policies in Brazil from the intersectoral guideline proposed to operationalize the decentralization and promote the constitutional principle. He drew a picture of scientific production in the field of Brazilian public policy, focusing on public management of intersectionality, through a search of articles published in scientific journals indexed in databases from 1988, historical and normative framework for analysis intersectoral this guideline in the law of creation of the Brazilian social protection services. The research analyzed the intersectoral approach building on the management of public policies. Such a theme makes it possible to rethink the operation of the implemented Brazilian public policies through advance directives proposals from the 1988 Constitution. This study concluded that scientific texts are in an incipient phase and concentrated in health, organized in political, administrative and epistemological earlier that the area of social and disconnected from social security assistance. Of which comes from research and reporting practices experiences, particularly those associated with the operating scale implementation of social policies. These intersectoral experiences of nature operating in public administration do not solve the structural problems of an economic society, only possible evidence inclusive political projects and situated in the defense of social rights guaranteed in the constitution.
Keywords: Políticas públicas; Política social; Intersetorialidade; Gestão pública; Revisão bibliográfica; Diretrizes organizacionais; Revisão de literatura; Public policy; Social policy; Intersectoriality; Public management; Organizational guidelines; Literature review; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL